A Rigid Trigonal‐Prismatic Hexagold Metallocage That Behaves as a Coronene Trap. (4th April 2019) - Ibáñez, Susana; Peris, Eduardo
Abstract: A trigonal‐prismatic hexagold cage was obtained by combining a triphenylene‐tris(N‐heterocyclic carbene) ligand and a carbazolyl‐bis(alkynyl) linker. The metallocage has a slot‐like cavity with a volume of about 300 Å 3 . The cage was used for the recognition of several polycyclic aromatic hydrocarbons. Due to the perfect dimensional match, the supramolecular complex shows a very high affinity for trapping coronene. Abstract : Eingefangen : Ein trigonal‐prismatischer Hexagoldkäfig mit einem spaltartigen Hohlraum wurde aus einem Triphenylen‐tris(NHC)‐Liganden und einem Carbazolyl‐bis(alkinyl)‐Linker hergestellt. Er kann für die Erkennung verschiedener polycyclischer aromatischer Kohlenwasserstoffe genutzt werden und hat die perfekten Dimensionen zum Einfangen von Coronen.